The Tendency Toward Tax Evasion in Jordan - Slehat, Yaser Ahmad Abed Alfattah (2009)
The main purpose of this study is to examine the tendency of Jordanian taxpayers toward tax evasion by investigate the influence of the following variables on tax evasion: (Age,gender, marital status, education, level of income, source of income, corruption and bribery,tax rate, penalty rate, probability of detection, fairness of tax system and government,religion, and ethics). The data was collected through distribution of questionnaires to 212 respondents in Jordan and processed using statistical package for social science (SPSS)software for the purpose of this study. By using Correlation and regression analysis, the findings show that there is a positive significant relationship between corruption and bribery, tax rate, penalty rate, probability of detection, fairness of tax system and government, religion, and ethics with tax evasion,whereas education and level of income significantly negative with tax evasion. No significance correlation but the relation was positive between marital status with tax evasion, while the other factors, age, gender, and source of income have no significance correlation but the relation was negative.